Ecology of luminous bacteria in penaeid shrimp grow-out systems of West Bengal, India - Abraham, T Jawahar; Gupta, Tapti Sen; Sasmal, Debasis (Indian Journal of Fisheries, 2011)
Occurrence and distribution of luminous bacteria (LB) from improved traditional,stagnant pond, modified extensive and semi-intensive shrimp grow-out systemsof West Bengal were studied. About 51% of pond water, 31% of pond sedimentand 22% of water samples had detectable level of LB. They were isolatedinvariably in all the diseased shrimp samples. The highest luminous bacterialcounts (LBC) were recorded in the water samples of semi-intensive system (log